Model dan Teknik Supervisi Pendidikan di Madrasah - Nur Izza Firdausi Hermawan; Wahid Murni; Indah Aminatuz Zuhriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Educational supervision is business assistance in supervising and coaching education stakeholders in increasing efforts to achieve educational goals. Of course, in carrying out supervision there are several models and techniques for implementing it. This research uses a qualitative approach by identifying techniques and models of educational supervision in madrasas by searching reference materials. books in the form of literature studies from related journals. The results of this research are an explanation of the supervision models and techniques used in schools/madrasahs. Some good supervision techniques are: 1) class visits, 2) school/madrasah visits, 3) individual interviews, and 4) group interviews.